All‐Solid‐State Fiber Supercapacitors with Ultrahigh Volumetric Energy Density and Outstanding Flexibility. Issue 9 (11th January 2019) - Pan, Zhenghui; Yang, Jie; Zhang, Qichong; Liu, Meinan; Hu, Yating; Kou, Zongkui; Liu, Na; Yang, Xin; Ding, Xiaoyu; Chen, Hao; Li, Jia; Zhang, Kai; et al.
Abstract: Fiber supercapacitors (FSCs) represent a promising class of energy storage devices that can complement or even replace microbatteries in miniaturized portable and wearable electronics. One of their main limitations, however, is the low volumetric energy density when compared with those of rechargeable batteries. Considering the energy density of FSC is proportional to CV 2 ( E = 1/2 CV 2, where C is the capacitance and V is the operating voltage), one would explore high operating voltage as an effective strategy to promote the volumetric energy density. In the present work, an all‐solid‐state asymmetric FSC (AFSC) with a maximum operating voltage of 3.5 V is successfully achieved, by employing an ionic liquid (IL) incorporated gel‐polymer as the electrolyte (EMIMTFSI/PVDF‐HFP). The optimized AFSC is based on MnO x @TiN nanowires@carbon nanotube (NWs@CNT) fiber as the positive electrode and C@TiN NWs@CNT fiber as the negative electrode, which gives rise to an ultrahigh stack volumetric energy density of 61.2 mW h cm −3, being even comparable to those of commercially planar lead‐acid batteries (50–90 mW h cm −3 ), and an excellent flexibility of 92.7% retention after 1000 blending cycles at 90°. The demonstration of employing the ILs‐based electrolyte opens up new opportunities to fabricate high‐performance flexible AFSC for future portable and wearable electronic devices. Abstract : An all‐solid‐state asymmetric fiber supercapacitor (AFSC) with a maximum operating voltage of 3.5 V is demonstrated, by employing an ionic liquid (IL) incorporated gel‐polymer as the electrolyte, which gives rise to an ultrahigh stack volumetric energy density of 61.2 mW h cm −3 . The demonstration of employing the IL‐based electrolyte opens up new opportunities to fabricate high‐performance flexible AFSC for future wearable electronic devices.